MODEL PROYEKSI PENDAPATAN PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA DI DINAS PENDAPATAN DAERAH (DISPENDA) PROVINSI BENGKULU - Karona Cahya Susena; Ahmad Soleh (UNIVED Press, 2017)
Karona Cahya Susena dan Ahmad Soleh; This study aims to describe the projection model in determining the Motor Vehicle income tax and transfer duties Dinas Pendapatan Daerah (Dispenda) Provinsi Bengkulu e in 2016-2020. The results of this study indicate that Trend Least Square method is more appropriately used to set targets in 2016-2020, where the calculation of trend Least Square for motor vehicle taxes in 2016 amounted to Rp. 176 189 057 021 and is increasing each year until 2020 sebesr Rp. 207 685 219 438. Acceptance of transfer tax to the name in 2016 amounted to Rp. 176 334 894 949 and 2020 sebesr Rp. 197 897 953 080, with all three (3) such methods are Moment Method, Least Square method and quadratic trend that shows an increasing trend from year 2016 to 2020, it indicates that a potential source of revenue that is expected to Bengkulu Province.Key Words: Motor Vehicle income tax and transfer duties